Pengembangan Media Pembelajaran LKPD Digital Berbasis Wizer.me pada Materi Kearsipan Kelas XI SMKN 62 Jakarta - Jihan Rahmawati; Roni Faslah; Mayang Riyantie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the development process of a Wizer.me-based digital student worksheet and to analyze its feasibility and practicality in Records Management subject for Grade XI MPLB students at SMKN 62 Jakarta. The study was motivated by the conventional nature of Records Management learning, which has been relying on printed textbooks and worksheets, making it less capable of facilitating procedural visualization, hands-on practice, and active student engagement. The study employed a Research and Development (R&D) method using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data were collected through questionnaires, observation, interviews, and documentation, involving content experts, media experts, and language experts as validators, as well as students as trial subjects. Validation results indicated feasibility percentages of 99.17% from the content expert, 87.5% from the media expert, and 93.33% from the language expert, all categorized as Very Feasible. Practicality test results reached 95.56% in the limited trial involving 12 students, and 93.61% in the field trial involving 36 students, both categorized as Very Practical. Therefore, the Wizer.me-based digital student worksheet is declared feasible